2021
DOI: 10.1158/1078-0432.ccr-20-4792
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Ib/II Study of Pepinemab in Combination with Avelumab in Advanced Non–Small Cell Lung Cancer

Abstract: biomarker analysis demonstrated improved tumoral infiltration of CD8+ T cells and supported the proposed mechanism of action of pepinemab, namely, to shift the tumor microenvironment toward immunity and away from immunosuppression thus enhancing immune checkpoint inhibition.Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…The combination of camrelizumab and chemotherapy including carboplatin and pemetrexed could also ameliorate the mPFS (11 months) of NSCLC patients without EGFR and ALK mutations ( 184 ). More interestingly, in a phase Ib/II study ( NCT03268057 (first posted: 31 August 2017) ), pepinemab that mainly treats Alzheimer’s disease and Huntington’s disease in combination with avelumab (an anti-PD-L1 antibody) was proved well-tolerated in NSCLC patients ( 185 ). Even though the patients’ mPFS was only 8.4 weeks in this trial ( Table 3 ), this clinical study provides a new option for the treatment of NSCLC ( Figure 3 ).…”
Section: Treatments For Lung Cancermentioning
confidence: 99%
“…The combination of camrelizumab and chemotherapy including carboplatin and pemetrexed could also ameliorate the mPFS (11 months) of NSCLC patients without EGFR and ALK mutations ( 184 ). More interestingly, in a phase Ib/II study ( NCT03268057 (first posted: 31 August 2017) ), pepinemab that mainly treats Alzheimer’s disease and Huntington’s disease in combination with avelumab (an anti-PD-L1 antibody) was proved well-tolerated in NSCLC patients ( 185 ). Even though the patients’ mPFS was only 8.4 weeks in this trial ( Table 3 ), this clinical study provides a new option for the treatment of NSCLC ( Figure 3 ).…”
Section: Treatments For Lung Cancermentioning
confidence: 99%
“…This change in the tumor architecture was associated with durable tumor rejection in murine Colon26 and ERBB2(+) mammary carcinoma models (46). Recently, a Phase Ib/II study of pepinemab (anti-Sema4D) in combination with avelumab (anti-PD-L1) showed that the combination therapy was well tolerated and exerted antitumor activity in immunotherapy-resistant and PD-L1-low NSCLC patients (76). However, the function of Sema4D on Treg responses in cancer is still unknown.…”
Section: Sema4dmentioning
confidence: 99%
“…For instance, the combination of Sema4D mAb with either CTLA-4 or PD-1 inhibitor abrogates tumor growth in murine oral cancer-1 mice by inhibiting MDSC recruitment and enhances CTL infiltration (44). Recently, the combination of lgG mAb targeting Sema4D (pepinemab) with PD-L1 inhibitor avelumab has been evaluated as a safe and tolerated synthetic therapy in phase II clinical trials of immunotherapy-resistant NSCLC patients (76). Another phase I trial (NCT03425461) has been registered on ClinicalTrials.gov.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Although CD100 has been described as a costimulatory ligand for DETC, its role in cancer appears to be mostly pro-tumorigenic as demonstrated by the antitumor activity of blocking anti-CD100 antibodies in mouse tumor models [ 52 , 59 ]. Based on these studies, an antagonistic anti-human CD100 antibody (pepinemab) is currently being tested in phase II clinical trials for the treatment of human cancers [ 123 , 124 ]. If successful in clinical trials, the effect of blocking anti-CD100 antibodies on inhibition of pro-tumor IL-17-producing γδ T cells versus antitumor IFNγ-producing γδ T cells will be of interest and may help inform which solid tumor indications are most suitable for treatment [ 61 ].…”
Section: Introductionmentioning
confidence: 99%